Water pressure evolution and structural failure characteristics of tunnel lining under hydrodynamic pressure. (December 2021) - Fan, Haobo; Zhu, Zhengguo; Song, Yuxiang; Zhang, Shiyu; Zhu, Yongquan; Gao, Xinqiang; Hu, Zhinan; Guo, Jiaqi; Han, Zhiming
Highlights: The evolution law of lining water pressure under hydrodynamic pressure is investigated. The failure characteristics of tunnel lining under hydrodynamic pressure is experimental explored. An optimized drainage scheme to reduce the water pressure at the invert is put forward, and the effect is analyzed. Abstract: With the frequent occurrence of heavy rainfall, the lining cracking, leakage, and buckling collapse accidents of water-rich mountain tunnels are becoming increasingly prominent. A large amount of surface water rushing into the tunnel in a short time and exceeding the drainage capacity of the tunnel is an important reason for the occurrence of water pressure diseases. To ascertain the failure characteristics of the lining structure under the condition of surface rainfall recharge and tunnel drainage, we designed a seepage model test system. The evolution law of water pressure behind lining, vertical displacement of invert and failure characteristics of structure under water pressure were studied. On this basis, the influence of the optimized drainage tunnel structure on the water pressure of the lining was further studied. The results show that the water pressure of the lining invert cannot be effectively reduced through the drainage system when the conventional drainage scheme is adopted, and the invert deforms and gradually cracks and fails under the action of hydrodynamic pressure. The cracking sequence of the lining structure is the invert center, the sidewall foot, the vault, and the sidewall. The type of cracks is mainly longitudinal, supplemented by circumferential and oblique. When the optimized drainage scheme is adopted, the water pressure at the bottom of the invert and the uplift displacement of the structure are significantly reduced, ensuring the safety of the lining structure.